(untitled) (Applied Biological Research, 2024)
The heart is considered an important reflexogenic organ and the stimulation of cardiac nociceptors is responsible for the elicitation of different cardiogenic reflexes. Most likely this is the basic reason behind different clinical presentations associated with heart failure, or myocardial infarction (MI). Clinically, heart failure due to myocardial ischemia is associated with bradycardia, hypotension, urge to pass urine, and stool. It is well established that different chemical substances like lactic acid, prostaglandins, bradykinin, and K+, are released during myocardial ischemia which, in turn, is responsible for the elicitation of cardiac pain that may result in different visceral and somatic reflexes. So, understanding the basic physiological mechanism behind such clinical association between cardiac ischemia-induced heart failure may help clinicians manage this fatal condition. This paper presents a comprehensive review on neurophysiological basis of different clinical presentations associated with MI-induced heart failure. The review also analyses the neural pathway for different cardiogenic reflexes which are associated with different clinical signs or symptoms associated with cardiac failure and thereby may be responsible for the diagnosis of early heart failure.